Bioproduto à base de óleo de andiroba como agente antimicrobiano e bio-revestimento para ovos comerciais - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
This study was divided into five chapters: the first (Chapter I) deals with the literature review, the second (Chapter II) concerns the diagnosis of the productive and economic profile of the andiroba oil chain in the Amazonas state (Brazil), the third (Chapter III) evaluates the effectiveness of a bioproduct with andiroba oil levels applied in different methods and periods for the conservation of eggs stored at room temperature, the fourth (Chapter IV) assesses different levels of oil in the bioproduct composition on egg quality, and the fifth (Chapter V) evaluates the effectiveness of an andiroba oil-based bioproduct (BPOA) applied to eggs stored for different periods and environments. Based on the results obtained in each chapter, important findings about the production and application of andiroba oil were highlighted, especially its use in egg conservation. Chapter II revealed that andiroba oil production in Amazonas is concentrated in three microregions: Juruá, Jutaí/Solimões/Juruá, and Purus, with Juruá being the main producer. Between 2010 and 2022, the price paid per kilogram of oil increased almost fourfold, and both the number of producers and the price paid are crucial factors for production. This production is still carried out using traditional methods and is predominantly sold in local markets, with the industry seeking expansion. Chapter III showed that BPOA is effective in conserving eggs stored for seven days at room temperature. Egg immersion was the most effective application method, especially with a 30-second application. However, high oil levels in BPOA and longer application times may affect the sensory acceptance of eggs. Chapter IV confirmed that BPOA improves egg conservation over seven days, with a 15% oil level in the formula being the most effective. BPOA maintains the physical and chemical quality of the eggs and reduces bacteriological concentrations. However, once again, sensory acceptance of the eggs may be compromised with high oil levels. Chapter V demonstrated that BPOA and refrigerated storage has a significant impact on maintaining egg quality. Refrigeration helps maintain moisture, reduce water activity, and slow down chemical and microbial reactions, as well as prevent bacterial contamination, including Salmonella spp. These factors significantly improves the conservation and safety of eggs compared to storage at room temperature without BPOA.
Bioproduct based on andiroba oil as an antimicrobial agent and bio-coating for commercial eggs
Keywords: .; .; .; CIENCIAS AGRARIAS: ZOOTECNIA; Amazônia; Avicultura; Biotecnologia; Carapa guianensis Aubl